Nodular Calcification in Saphenous Vein Graft Successfully Treated by Percutaneous Coronary Intervention. (8th November 2018) - Yamamoto, Ko; Natsuaki, Masahiro; Serikawa, Takeshi; Okabe, Masanori; Yamamoto, Yusuke
Abstract : Nodular calcification is sometimes detected in the native coronary artery. However, it is very rare to find in a saphenous vein graft (SVG). We herein report a rare case of stable angina pectoris (AP) due to nodular calcification. A 75-year-old man who had previously undergone coronary artery bypass grafting was admitted to our hospital due to stable AP. On angiography, significant stenosis was detected in the proximal SVG. Based on the findings of coronary angiography and optical coherence tomography, a red thrombus was suspected at the culprit lesion. However, nodular calcification was also suspected, as there were calcifications around the lesion. As intravascular ultrasound showed the protruding calcification, which we judged to be a nodular calcification, the calcified SVG lesion was successfully treated by percutaneous coronary intervention without any complications. Nodular calcification should be considered as a potential cause of AP, even when located in a SVG.